SUNTIK MATI (EUTHANASIA) DITINJAU DARI ASPEK HUKUM PIDANA DAN HAK ASASI MANUSIA DI INDONESIA - Tjandra Sridjaja Pradjonggo (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
Euthanasia problem has existed since the health system faces an incurable disease, while the patient is dying and torture. In such situations, it is not uncommon patient begged to be released from this suffering and did not want an extended life again or in other circumstances in patients who are not aware, families of patients who did not have the heart to see patients suffering deathbed ask the doctor or nurse not to continue treatment or if necessary, provide drugs to hasten death. From this emerged the term euthanasia, which took off a person’s life to be free from suffering or dying well. From the study of this thesis can be concluded that the lethal injection, or more commonly called euthanasia if viewed from the aspect of criminal law and human rights in Indonesia are still having a debate that has not found the end, because of the provision of human rights by the opposition national laws, especially the Criminal Code in force in Indonesia, but basically that the act of euthanasia is still Brazilians is prohibited in the criminal justice system and health laws that exist in Indonesia, whatever and however excuse used and anyone who filed either personally want themselves or family everything is still forbidden to do anything syringe the dead, even the health workers are still prohibited from lethal injection for any reason